Reflections for busy educators : 180 affirmations to help you through the school year - Lordahl, Jo Ann. (Thousand Oaks, Calif. : Corwin Press, 1995)
This original book is designed to facilitate teachers' personal, moral, ethical and spiritual development by inviting them to consider education from both conventional and innovative perspectives. Jo Ann Lordahl offers encouragement and strength to teachers as they begin each working day.--Goodreads.
Includes bibliographical references.
Keywords: Education -- Quotations, maxims, etc; Quotations, English